Kant's Religion within the boundaries of mere reason : a critical guide - Michalson, Gordon E., 1948- (New York : Cambridge University Press, 2014)
This volume provides a synoptic view of Kant's major work of religious thought.
Chapter 10 Kant's religious constructivismChapter 11 What does his Religion contribute to Kant's conception of practical reason?; Chapter 12 Culture and the limits of practical reason in Kant's Religion; Bibliography; Index
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Kant, Immanuel, -- 1724-1804.; Religion innerhalb der Grenzen der blossen Vernunft (Kant, Immanuel); Religion -- Philosophy; Good and evil; Religion; Religion -- Philosophie; Religion; religion (discipline); RELIGION -- Philosophy; Good and evil; Religion; Religion -- Philosophy